An Apology for Unreal Wages: Building Labourers and Living Standards in the Southern Low Countries (1290–1560) - Geens, Sam; Blondé, Bruno (International review of social history, 2025)
Although real wages have long been a cornerstone of our understanding of the premodern economy, in recent years historians have become sceptical about their usefulness as a proxy for living standards. One of the main concerns is that, before industrialization, most households did not depend on wages but were self-employed. This article therefore proposes a new methodology to test the representativeness of real wage series for the general population by comparing changes in the purchasing power of builders’ wages with the relative position of building labourers in tax lists. Not surprisingly, it confirms their exceptional position, which evolved according to remuneration. Instead of disregarding the unreal wages, the methodology shows a promising path forward. The relationship between changes in wage income and the relative position in fiscal sources can be exploited to identify other groups who were or became dependent on this type of labour. Accordingly, it holds the potential to retrace shifts in the functional distribution of income and the wage systems for different groups in the premodern economy.